Asgardia: The Problems in Building a Space Society - Kandi Kirana Larasati; Amadda Ilmi (CV Rewang Rencang, 2020)
Asgardia is a region that proves that the progress of human thinking is very visionary. It is a region in the space called capable and will be able to be a place to live for humans. The truth has not been fully proven, but the payment of regulation and implementation continues. Because it has the support of various parties and communities that can be said to no longer want to live on earth. The way of recruitment is also unique, the Asgardia team has formed an official website for registration to become prospective citizens in the region, the number is not small. But it still continues to be a concern for many parties to explore whether it is a hallucination or reality. While the regional engagement conference is also running, which can be seen and immortalized in videos uploaded on YouTube. They have also determined a kind of state emblem to form of government, but the official status of